Steady Laminar Natural Convection Heat Transfer inside Air-Filled Horizontal Triangular Enclosure Containing Three Cylindrical Rods - Abood, Falah Assi; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2011)
The natural convection heat transfer from horizontal isothermal three cylindrical rods inside equilateral triangular enclosure has been studied numerically. The enclosure is filled with air, and the heated rods are located at equal distances (E) from triangle center. A finite element software package (FLEXPDE) is used in the present study to solve the set of non-linear equations governing the process. Solutions are obtained for aspect ratio D/H=1/6 and range of distance E=0.2-0.6 and Rayleigh (Ra) number changes from 103 to 106. The effect of Ra and E were examined. Results are presented by streamlines, isotherms and Nusselt number and it indicates that the Nusselt number is significantly increase with increasing both Ra and E. A comparison of the Nusselt number was made with that obtained by [7], and showed substantial improvement to about 65% in some cases.